DEVELOPMENT OF CAREER MASK MEDIA TO IMPROVE STUDENTS CAREER EXPLORATION - Aji mulya pratama; Eva Kartika Wulan Sari; Ajeng Intan Nur Rahmawati (OPTIMA: Journal Of Guidance and Counseling, 2023)
This research was motivated by the low level of career exploration at SDN Dempo Timur 1. The data was obtained from the distribution of needs assessments along with interviews with three teachers. The purpose of this development research is to produce a product in the form of a set of career masks to enhance the career exploration of elementary school students which has been validated based on the attractiveness, convenience, accuracy and effectiveness of career masks. Based on this needs assessment, this research is important to increase the career exploration of elementary school students. This development research uses a research method developed by Borg and Gall. Of the 10 stages of the method, the researcher summarized the 6 stages in this study. Namely, data collection, planning, product development, expert testing, product revision, and effectiveness of media use. The results of this study are that the career mask media meets the acceptable standards of accuracy, attractiveness and comfort. In addition, this career mask has been through a small group test with effective results to increase career exploration for elementary school students